Proposal for the creation of a virtual library at the Universidad Latinoamericana de Ciencia y Tecnología ULACIT - Fonseca Quirós, Xinia Lidieth (2004)
This document is a summary of the final graduation work, which had as its purpose the creation of a virtual library for the Universidad Latinoamericana de Ciencia y Tecnología (ULACIT). In the first instance, the author details the importance of the creation of this library, highlighting the benefits that its creation would bring to the institution. Finally, she refers to the stages for the development of the project, making known the methodology and tools used for its implementation.